THEORETICAL AND PRACTICAL FOUNDATIONS OF FOOTBALL AND METHODS OF TEACHING IT - A. M. Rayxonov (American Journals, 2025)
Soccer is a sport in which two teams try to score a goal. Football is the most famous and most watched sport in the world. It is played in many leagues and competitions around the world covering different ages and levels.
Keywords: Theoretical, practical foundations, football, methods of teaching it.